Efektivitas Penerapan Standar Akuntansi Pemerintah tentang Transparansi Pelaporan Keuangan Desa: Pendekatan Pemodelan Persamaan Struktural - Tetelepta, Johanis M.; Talakua, Victor Amanusa (Journal of Applied Accounting, 2025)
This study examines the effectiveness of implementing Government Accounting Standards on the transparency of village financial reporting using a Structural Equation Modeling approach involving 295 respondents from village governments in Bandung Regency and West Bandung. The analysis results indicate that human resource competence, internal control systems, information technology support, and leadership commitment significantly contribute to the effectiveness of implementing Government Accounting Standards, with an R-square value of 72.4 percent. The empirical findings confirm that the implementation of Government Accounting Standards has a positive and significant effect on the transparency of village financial reporting, mediated by improvements in the quality of financial reports.The structural model shows that the effectiveness of implementing Government Accounting Standards can explain 63.2 percent of the variation in village financial reporting transparency. Multi-group analysis reveals that village characteristics moderate the relationship between the implementation of Government Accounting Standards and transparency, while villages with higher fiscal capacity show a stronger effect. The practical implications of this study emphasize the urgency of enhancing village apparatus capacity through continuous training programs and providing adequate technological infrastructure to support the improvement of village financial management quality. Keywords: Government Accounting Standards, Financial Reporting Transparency, Structural Equation Modeling